PWM DC-AC converter regulation using a multi-loop single input fuzzy PI controller - Md. Ayob, Shahrin (Korean Institute of Power Electronics, 2009)
This paper presents a PWM dc-ac converter regulation using a Single Input Fuzzy PI Controller (SIFPIC). The SIFPIC is derived from the signed distanced method, which is a simplification of a conventional fuzzy controller. The simplification results in a one-dimensional rule table, that allows its control surface to be approximated by a piecewise linear relationship. The controller multi-loop structure is comprised of an outer voltage and an inner current feedback loop. To verify the performance of the SIFPIC, a low power PWM dc-ac converter prototype is constructed and the proposed control algorithm is implemented. The experimental results show that the SIFPIC performance is comparable to a conventional Fuzzy PI controller, but with a much reduced computation time.